2003
DOI: 10.1046/j.1440-1843.2003.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement in surfactant measurements of sputum induced with hypertonic and normal saline

Abstract: We conclude that DPPC concentration of sputum can be easily measured in induced sputum and that the use of hypertonic saline does not influence the DPPC levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…DPPC can be adsorbed (reversibly bound) onto the epithelial layer or occur in the ‘free’ state 8 . We have previously shown that free DPPC can be easily measured in airways 10,11 and that increased DPPC is associated with increased eosinophilic inflammation in children with asthma, 11 possibly as an inherent lung mechanism for epithelial protection. Animal studies have shown that DPPC levels progressively increase in response to chronic lung injury 9,12 …”
Section: Introductionmentioning
confidence: 99%
“…DPPC can be adsorbed (reversibly bound) onto the epithelial layer or occur in the ‘free’ state 8 . We have previously shown that free DPPC can be easily measured in airways 10,11 and that increased DPPC is associated with increased eosinophilic inflammation in children with asthma, 11 possibly as an inherent lung mechanism for epithelial protection. Animal studies have shown that DPPC levels progressively increase in response to chronic lung injury 9,12 …”
Section: Introductionmentioning
confidence: 99%